Crisis and poverty: With reference to Latin America. (September 2019) - Koo, Hyevin; Oh, Jinhwan
This study analyzes the relationship between four types of economic crises and four poverty indices in an effort to determine which type of crisis most affects the poor, and find possible solutions. This study is particularly concerned with Latin American countries in which International Monetary Fund bailout programs have failed due to repeated crises, longer lasting inflation, and most of all poverty. The results indicate an apparent worsening trend in poverty measures due to the crises. Among several types of crises, debt crisis and currency crisis play larger roles than others, particularly with the headcount poverty ratio US$3.10.